2021
DOI: 10.1111/jeb.13890
|View full text |Cite
|
Sign up to set email alerts
|

Sequence dynamics of three influenza A virus strains grown in different MDCK cell lines, including those expressing different sialic acid receptors

Abstract: Viruses are often cultured in cell lines for research and vaccine development, and those often differ from the natural hosts or tissues. Cell lines can also differ in the presence of virus receptors, such as the sialic acid (Sia) receptors used by influenza A viruses (IAV), which can vary in linkage (α2,3‐ or α2,6‐linkage) and form (N‐glycolylneuraminic acid [Neu5Gc] or N‐acetylneuraminic acid [Neu5Ac]). The selective pressures resulting from passaging viruses in cell types with host‐specific variations in vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…3b). These findings are consistent with a prior study that demonstrated human seasonal H1N1 and H3N2 IAVs, which bind exclusively to Neu5Ac, developed adaptive HA mutations when passaged in MDCK cells expressing Neu5Gc (17). Conversely, an enzootic canine H3N2 IAV, which binds to both Neu5Gc and Neu5Ac, did not exhibit significant HA mutations under the same conditions.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…3b). These findings are consistent with a prior study that demonstrated human seasonal H1N1 and H3N2 IAVs, which bind exclusively to Neu5Ac, developed adaptive HA mutations when passaged in MDCK cells expressing Neu5Gc (17). Conversely, an enzootic canine H3N2 IAV, which binds to both Neu5Gc and Neu5Ac, did not exhibit significant HA mutations under the same conditions.…”
Section: Resultssupporting
confidence: 92%
“…We hypothesized that the expression of Neu5Gc hinders replication in H7 viruses that exclusively bind to Neu5Ac but do not affect those that bind to both Neu5Ac and Neu5Gc. To test this, we compared the growth kinetics of two mutants (rgCk/WX13-V179I and rgCk/WX13-A122N) and their parent virus, rgCk/WX13, on MDCK-Gc, a cell line expressing Neu5Gc (17), and MDCK-wt, the wild-type cell line without Neu5Gc expression. We also included A/mallard/New Jersey/A00926089/2010 (H7N3) (HA)×PR8 (H7N1) (rgMall/NJ10), with the HA of an H7 virus from a mallard ( Anas platyrhynchos ), and A/chicken/Heinan/ZZ01/2017(H7N9)(HA)×PR8 (H7N1) (rgCk/HN17), with the HA of another AH/13- lineage H7N9 virus from chicken (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, experimental infections of a turkey-derived H9N2 virus has also shown that the highest number of nonsynonymous changes occurred in samples from infected ducks, most likely reflecting shifts in host species [ 11 ]. Similarly, experimental passage of avian, canine, or seasonal human influenza A viruses in embryonating eggs or immortalized cell lines have shown the preponderance of nonsynonymous changes that has been attributed to shifts in viral replication from its natural host to an experimental culture system [ 7 , 74 , 75 ]. This increase in nonsynonymous changes coinciding with a change in host has been further documented for a variety of viruses including severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) [ 20 ], Newcastle disease virus [ 13 ], bovine viral diarrhea virus [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eradication currently seems unrealistic given the vaccine efficiency in blocking infections and the possibility for presence in animal reservoirs, which could differentially impact virus evolution. For instance, differences in host‐cell receptors can drive divergence among influenza virus lineages as they adapt in vitro (Barnard et al). The host itself is only part of the equation and for an ssRNA plant virus the habitat in which these plants are located also shapes evolutionary dynamics (Peláez et al).…”
Section: Eradication Requires Will (And Funding)mentioning
confidence: 99%